Pembuatan E-Transaksi Pada PT. Ajusta Tirta Berbasis Hybrid Menggunakan Plugin Webview - Agung Andrianto; Dwi Lestari; Raditya Galih Whendasmoro (Eksplorasi Teknologi Enterprise & Sistem Informasi (EKSTENSI), 2022)
The e-transaction information system is all company activities aimed at carrying out e-transaction processes within the scope of pt.ajusta tirtamas because at this time there are still several processes that are carried out manually and the transaction and sales files have not been integrated. From the existing problems, it is designed and built an e-transaction information system that is expected to handle these problems. In defining requirements and analyzing system development, data collection methods were carried out by means of observation, interviews and literature review from various sources of information. For the analysis and design method using Unfield Modeling Language (UML), the e-transaction information system at pt.ajusta tirtamas uses the Hypertext Preprocessor programming language, Java, and MySQL as the database.